Production optimization of probiotic soft cheese made from goat's and cow's milk - Ida Drgalić; Ljubica Tratnik; Rajka Božanić; Sandra Koruga (Mljekarstvo)
The aim of this study was to determine optimal rennet share and fat content in milk for probiotic soft cheeseproduction made from goat's and cow's milk using DVS mixed probiotic culture ABT-4 (Lactobacillus acidophilus, Bifidobacterium spp. and Streptococcus thermophilus), with desirable sensory properties, which will be acceptable by consumers. The best sensory scores had samples of probiotic soft cheese produced in laboratory conditions from milk with 1% of milk fat, pasteurized at 65°C/30 min., fermented at 38°C with 2% culture. To achieve characteristic consistency of traditional soft cheese, 0.01% of rennet was added to goat's milk. Probiotic soft cheese made from cow's and goat's milk, produced under optimal conditions, were 100% acceptable by the tested consumers.